Effects of magnesium and potassium sulfates on oil recovery by water flooding - El-Abbas A.A. Moustafa; Shedid A. Shedid (Egyptian Journal of Petroleum)
Conventional water flooding has been applied successfully worldwide using sea water and/or formation brine. Two processes are proposed to improve oil recovery by water flooding such as; lowering water salinity as LoSal (300 to 5,000 ppm) and changing concentration of cations and/or anions as designer water.This experimental study investigates combined effects of concentration of magnesium and potassium sulfates with consideration of sodium chloride salinity on oil recovery by water flooding. To achieve the objectives of the study, nine flood experiments were conducted using actual sea water and synthetic water injected through actual sandstone reservoir cores. Three experiments were achieved using actual Egyptian sea waters of Al-Obayied, Balteam and Abo Rudies to investigate the combined effect of magnesium and potassium sulfate concentration on oil recovery. Three experiments were conducted to study the combined effect of Magnesium sulfate and sodium chloride contents on oil recovery. In addition, three other experiments were carried out to investigate the effect of potassium chloride concentrations associated with sodium chloride salinity (higher than the 5000 ppm stated for low salinity process) on oil recovery.The results revealed that sea water of higher content of magnesium sulfate and potassium sulfate increases the oil recovery by water flooding. In addition, the increase of concentration of magnesium sulfate with lower sodium chloride increases the oil recovery by designer water injected containing sodium chloride. It is also concluded that the increase of potassium sulfate increases the oil recovery. The increment in oil recovery by increase of magnesium, and/or potassium sulfate is attributed to wettability alteration to more water-wet, higher pH condition and also to the decrease in sodium chloride associated in the same water injected.The application of the attained results will have real importance in designing the concentration of magnesium and/or potassium concentration of the designer water injected with consideration of sodium chloride salinity of the reservoir. Keywords: Water flooding, Designer water, Low salinity, Oil recovery